Os bestiários de Guimarães Rosa em Ave, Palavra - Pereira, Ivani Maria (2014)
This dissertation aims to reflect upon the presence of animals in Literature, seeking to elucidate compositional elements of selected texts from the work of the writer João Guimarães Rosa in which the bestiary theme, mainly, inserted in new literary writing, can be discussed. In order to do that, firstly we will travel, in a concise way, through Rosa´s biography and also we will privilege a perspective that aims at thinking the presence of animals in the literary journey of Guimarães Rosa. Following that we will present his last work, Ave, Palavra, whose texts portray the animal theme intensely. More than that, we magnified our view to the existing relationship between Man and animal in a modern perspective since Rosa´s texts allow us to reflect those biases because of its contents whose aesthetic procedures dialogue directly with the characteristics of modern literary construction or, at least, renewed textual configurations. After, we reflected upon literary genres, contemplating, specially, the poetic prose in Rosa´s works, enabling better understanding about the issues that round Rosa´s zoopoetic. It was imperatively necessary, before investigating Rosa´s bestiary specifically, a conceptual view and a historical resumption about the bestiary´s genre, focusing on the medieval times, subsequently to a contextualization of zooliterature, revisited and updated; lastly, upon the analysis of the texts Aquário (Berlim) and Aquário (Nápoles) , from Ave, Palavra, we sought to highlight Rosa´s style of bestiary and also the light of the investigative project of ecocriticism. Therefore, we worked with the complexity of Guimaraes´Rosa writings regarding the bestiaries, having as ballast, issues raised on texts from his literary career and, above all, from his posthumous work, Ave, Palavra, reflecting about the boundaries between human and non human, which enables an interpretative eye upon the picture of the modern man.